The Effect of the E-Module-Assisted Guided Inquiry Model through Student Learning Outcomes in Substance Pressure Material - Rafiqa Nurhidayah Hasibuan; Ridwan Abdullah Sani (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
This research aims to analyze the influence and increase in student learning outcomes using the guided inquiry model assisted by e-modules through the Professional Flip PDF application on substance pressure material. The research used a quasi-experimental method with a two-group pretest-posttest design. The sampling technique uses random cluster sampling. The research sample consisted of two classes, namely the VIII-4 experimental class with 31 students and the control class VIII-2 with 29 students. The research instrument uses a learning outcomes test instrument with 20 multiple-choice questions. The results of the pretest mean value of the experimental class were 47.41 with a standard deviation of 9.02, and the average value of the control class was 41.03 with a standard deviation of 8.80. The results of learning through hypothesis testing obtained tcount> ttable (6.59 <1671) so that Ha is accepted and rejects Ho. In conclusion, there is an influence of the assisted guided inquiry model e-module on student learning outcomes on material pressure material.